Differences in Tooth Brushing With Different Bristle Hardness in Ciburial 01 Elementary School Students, Bandung District - Marlin Himawati; Faiqa Aliifah; Henri Hartman (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Dental and oral health problems in 5-14 years old are tooth decay, cavities, gums that bleed easily when brushing teeth and swollen gums. One of the causes of dental and oral health problems is plaque. Plaque can be overcome by brushing teeth. The purpose of the study was to determine the difference in brushing teeth with different bristle hardness in students of the State Elementary School, (hereinafter abbreviated as SDN) Ciburial 01 village under the guidance of the Faculty of Dentistry, General Achmad Yani University. Materials and Methods: The type of research used was a Quasi-Experimental. Data were analyzed descriptively using the cross-sectional study method with measurements before and after brushing teeth in students of SDN Ciburial 1. Students of SDN Ciburial 01 will be divided into two equal groups. The first group uses a soft-bristled toothbrush and the second group uses a medium-bristled toothbrush. Furthermore, the assessment was carried out using the Quigley Hein plaque index modified by Turesky Gilmore Glickman. The respondents studied were 100 students who were not included in the exclusion criteria. Results and Discussion: The results of the study showed that students of SDN Ciburial 01 who experienced a decrease in plaque index had a different picture in students who brushed their teeth using a medium-bristled toothbrush (96%) with students who used a soft-bristled toothbrush (78%). Conclusion: The conclusion of this study is that a medium-bristled toothbrush is considered better at cleaning teeth than a soft-bristled toothbrush.